Fully stretchable and highly durable triboelectric nanogenerators based on gold-nanosheet electrodes for self-powered human-motion detection. (December 2017) - Lim, Guh-Hwan; Kwak, Sung Soo; Kwon, Nayoung; Kim, Taekyung; Kim, Han; Kim, Seong Min; Kim, Sang-Woo; Lim, Byungkwon
Abstract: A patchable triboelectric nanogenerator (TENG) is highly promising for self-powered human-motion detection, but it may undergo repeated stretching/releasing cycles during daily activities of a human, which may lead to mechanical fracture of each component and degradation in electrical output performance of the TENG device. Here, we report a fully stretchable and durable triboelectric nanogenerator (TENG) with gold (Au) nanosheets (NSs) embedded into both PDMS matrix and micropyramid-patterned PDMS. It was found that a new design of the Au NS electrodes dramatically improves the mechanical flexibility and stretchability, enabling to achieve the outstanding output stability of the Au NS electrode-based TENG (Au NS-TENG) during 10, 000 cycles of repeated pushing and stretching tests. Our fully stretchable and durable Au NS-TENGs were successfully applied to the hand joints that can be used in the self-powered human-motion detection processes for wearable applications. Graphic abstract: Fully stretchable and durable triboelectric nanogenerator with gold nanosheet embedded into both PDMS matrix and micro pyramid patterned PDMS has been successfully demonstrated in both pushing and stretching modes, then the durability test with 10, 000 cycles. As our device is applied to hand joints, the possibility of self-powered systems as power source for wearable applications has been shown. Highlights: We report a fully stretchable and durable triboelectric nanogenerator (TENG). The TENG consisted of gold nanosheet (Au NS)-embedded elastomer electrodes. Au NS-TENG showed excellent output stability during pushing and stretching tests. Au NS-TENGs were successfully applied for self-powered human-motion detection.